DIMENSI PEMBAHARUAN DALAM PENINGKATAN MUTU PENDIDIKAN - Budi Budi (Hijri, 2019)
Education is a conscious and well-planned endeavor to create a learningatmosphere and learning process so that students actively develop their potentialto possess religious spiritual strength, self-control, personality, intelligence, andskills necessary for himself, society, nation and state. In the education of qualitynot only seen from the teacher, but to realize the purpose of education in Indonesiaare many of the most important factors and very influence is the education force,teachers, curriculum, school principals, infrastructure facilities, Stakeholders andmany other factors. In conducting learning activities. The renewal of educationaims to know anything that should be the main concern and change needed by theeducation unit to make education quality and qualified.